Moral Decadence of Adolescents in the Digital Era: Ethical Challenges and Character Education Strategies in Senior High Schools - Sulaiman; Dwi Sri Wahyuni; Karno Susanto; Nurkholisah; Muslih Hidayat; Noorseha Ayob (Mimbar Ilmu, 2026)
This research is motivated by the increasing phenomenon of moral decadence among adolescents, a result of the influence of modernization and digitalization, which causes a decline in the values of empathy, responsibility, and self-control. The purpose of this study is to analyze adolescents' digital behavior, understand its impact on moral development, and formulate effective character education strategies within the high school context. This research uses a qualitative approach with a phenomenological design. The research subjects consisted of teachers and students who were selected purposively based on the intensity of gadget use and involvement in digital activities. Data was collected through in-depth interviews, participatory observations, and documentation, then analyzed using Miles and Huberman's interactive model. The results of the study show that excessive digital behavior lowers moral sensitivity and triggers the emergence of moral disengagement mechanisms. However, reflective literacy activities, collaborative learning, and religious arts can help re-cultivate ethical awareness and positive character. This study highlights the importance of integrating digital moral literacy and teacher role models to enhance the moral integrity of adolescents in the digital era.